PINJAMAN ONLINE DAN KEKERASAN PENAGIHAN URGENSI REFORMASI HUKUM DALAM PERSPEKTIF HAK ASASI MANUSIA - yuliana kemalasari, ni putu; Hoesein, Zainal Arifin (VYAVAHARA DUTA, 2025)
Online Loans (Pinjol) are one form of financial technology development that was born to provide easy access to financing for the community. However, behind that, the growth of Pinjol is not accompanied by the growth of an adequate legal system. So that it has an impact on practices that lead to violations of the law such as violence, intimidation and even have an impact on human rights violations. This study was conducted to examine the urgency of legal reform regarding collection regulations on online loans that have an impact on human rights violations. This study uses a normative legal research method with a legislative approach. Based on the results of the study, it was concluded that the current regulations relating to collection in online loans, namely PJKO No. 10 / PJOK.05 / 2022 concerning Information Technology-Based Joint Funding Services, have not been fully able to provide legal protection for consumers from acts of violence in terms of collection, especially in terms of sanctions and law enforcement. Therefore, legal reform is needed based on the principles of justice, proportionality, and respect for human rights. The reform must include the establishment of more specific legal instruments, strengthening supervisory institutions, and providing harmonization between legal instruments and human rights.